Optical soliton solutions of complex Ginzburg-Landau equation with triple power law and modulation instability - Onder, Ismail; Esen, Handenur; Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (SPRINGER, 2024)
This paper examines the complex Ginzburg Landau equation, which describes pulse propagation inside a fiber with the triple power law of self-phase modulation. Since the effect of parameter selection has become very important in relevant model studies recently, self-phase modulation has been added to the complex Ginzburg Landau equation, which has been studied in the literature, and it is aimed at investigating the analytical solutions of the presented equation. Adding the triple power law of the self-phase modulation parameter to the model, in addition to existing studies in the literature, emphasizes the innovative aspect and importance of the study. The first aim is to reveal bright and singular solitons using the new Kudryashov method. The new Kudryashov method is a technique that is frequently used in the literature, is effective for generating analytical solutions, provides ease of operation, and can be applied to a wide class of nonlinear partial differential equations. The second goal is to show that the obtained solutions have modulation stability. By using modulation instability analysis, the gain spectrum is formed for different parameter values. Graphic presentations support the findings. Moreover, bright and singular soliton portraits are demonstrated with 3D and 2D graphs. The novelty of the study lies in the fact that the relevant model has not been studied before with an effective method such as the new Kudryashov method, and the modulation instability has been studied for the first time.
Keywords: The new Kudryashov method; Self-phase modulation; Gain-spectrum; Detuning effect; Soliton; SELF-PHASE-MODULATION; SCHRODINGER; TURBULENCE; STABILITY; PULSES; Engineering; Physics; Optics